PENGARUH AGRESIVITAS PAJAK TERHADAP CORPORATE SOCIAL RESPONSIBILITY : UNTUK MENGUJI TEORI LEGITIMASI (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Intan Ayu Utari; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
This study aims to examine the influence of corporate tax aggressiveness with corporate social resposibity (CSR): to test legitimacy theory. Independent variabel used in this study is the tax aggressiveness that measured usingproxy of effective tax rates. Dependent variable in this study is the corporate social responsibility (CSR). This study used one control variables ROA.            This study is a replication of the study by Lanis and Richardson (2013) and use 159 manufacturing companies that listed on the Indonesia Stock Exchange in the period 2011-2013 as the sample. Samples were selected by purposive sampling method and finally obtained 53 manufacturing companies per year that fulfill the criterias. Data were analyzed using ordinary least square regression analysis model.            This study showed that the aggressiveness of corporate taxes significantly and positively related to CSR. Companies that have a high level of aggressiveness resulting company would disclose CSR greater than the firm that does tax aggressiveness. This does not justify the legitimacy of the theory in the context of tax aggressiveness.